Association between sleep behaviors and adiposity indices among U.S. adults: a cross-sectional study - Xu, Shenghao; Lin, Jie; Xu, Qibo; Zhao, Kai; Xiao, Jianlin (Frontiers in Nutrition, 2025)
ObjectivesThis study aimed to clarify the relationship between sleep behaviors and adiposity indices.MethodsWe analyzed NHANES data from 2011 to 2018 for adults aged 20–80, assessing BMI, waist circumference (WC), lean mass, and body fat percentage with DEXA scans and physical measurements. Sleep duration was categorized into short (<7 h), normal (7–9 h), and long (>9 h), as well as their sleep status based on questionnaires. Furthermore, we examined the interaction effects between sleep duration and sleep patterns.ResultsAmong 19,951 participants providing BMI and WC data, and 10,716 for lean mass and body fat percentage, short sleep duration correlated with higher BMI (β = 0.56, 95% CI: 0.36–0.76), WC (β = 0.90, 95% CI: 0.43–1.37), and lean mass (β = 0.70, 95% CI: 0.32–1.07). Individuals with sleep disorders showed increased values across all indices: BMI (β = 0.93, 95% CI: 0.72–1.13), WC (β = 2.40, 95% CI: 1.92–2.88), lean mass (β = 0.71, 95% CI: 0.30–1.12), and body fat percentage (β = 0.64, 95% CI: 0.37–0.90). No significant interaction effects were found between sleep duration and sleep disorders.ConclusionOur findings indicate that individuals with short sleep duration and sleep disorders are likely to carry a higher weight burden, indicating potential targets for addressing obesity-related health issues.